Abrupt change of a thermal front in a high-biomass coastal zone during early spring - Li, Jian; Li, Peiliang; Bai, Peng; Zhai, Fangguo; Gu, Yanzhen; Liu, Cong; Sun, Ruili; Wu, Wenfan (Frontiers in Marine Science, 2022)
Coastal fronts play vital roles in local biogeochemical environment. An abrupt change of Zhejiang-Fujian coastal front (ZFCF) during early spring was well captured by multi-source satellite-retrieved sea surface temperature images. Here in this study, we investigated the mechanism of the abrupt decay with a combination of satellite observation and numerical simulation. Correlation analysis of long-term reanalysis data indicates that the variability of wind, heat flux and the Zhejiang-Fujian coastal current (ZFCC) have significant relationships with the variation of ZFCF in winter. Following heat budget analysis points out that net heat flux and horizontal advection are important in determining the net temperature tendency difference between two water masses of ZFCF during this process. To further explore the intrinsic physical roles of different dynamic factors, a comprehensive numerical investigation was conducted. Compared with the observations, the model reproduced the abrupt change process of the ZFCF satisfyingly. Sensitive experiments reveal that the weakening of the ZFCC, caused by the relaxation of the monsoon, contributes to the abrupt decay of ZFCF in the first half period, and heating effect of the Kuroshio Intrusion (KI) water gives rise to the following half period of the decay under the recovered monsoon. Further, with the impact of the KI water after the change, the ZFCF can be maintained even if the ZFCC is weak, whereas in January, the contribution of the KI water to the formation of the ZFCF seems to be limited under the prevailing monsoon. Besides, the riverine discharge and the tidal forcing can also modulate the spatiotemporal variation of ZFCF, the decrease of the river input also intensifies that decay, while tides fix the front at a specific depth.